Without Frontiers? Travelling with birds and Emil Nolde - Ridley, Hugh (Cadernos de Literatura Comparada, 2016)
This paper is concerned with comparisons across the cultures, with travel, and with the idea of the exotic. It discusses bird-pictures by a Swedish artist and by the German Expressionist Emil Nolde, and suggests two different routes to the exotic, and questions the place of travel in that experience.